Individual Behavior Of Female Sumatran Orangutan (Pongo abelii L.) With Management System In Siantar Zoo - Arlen Hanel John (International Journal of Ecophysiology, 2021)
The Sumatran orangutan (Pongo abelii) is an endangered species due to the destruction of its forest habitat and deforestation. Various conservation efforts have been made to prevent the orangutan extinction,such as ex-situ conservation in Siantar Zoo.This study aims to determine the behavior of individual female orangutans at Siantar Zoo with a management system. The observatuons was conducted for 14 days in August with the focal animal sampling method and data recorded using the Instantaneous method.The results showed the overall frequency of individual female orangutan behavior were resting (40%), eating (35%), moving (14%), special (6%), self care (4%) and pooping (1%). The behavior of individual female orangutans is influenced by the number of visitors, namely the resting behavior of the crowded visitor category 39,15%, medium category 41.81% and quiet 39.68%. The eating behavior of the crowded visitor category is 37.80%, the medium category is 33.56% and the quiet category is 34.68%. The moving behavior in the quiet, medium and crowded categories is 14.18%; 12.85%; 11.67%. The specific behavior for the quiet, medium and crowded categories was 6.19%; 5.55%; 5.59%. Self-care behavior in the crowded visitor category is 4.34%, the medium category is 4.60% and the quiet category is 4.01%. The behavior of pooping in the crowded category is 1.45%, in the medium category is 1.62% and in the quiet category is 1.27%.The female orangutan management system at Siantar Zoo is analyzed as having a fairly good and regular system. The cage management has met the minimum requirements and the female orangutan has a good body weight and has never been infected with a serious disease.